2021
DOI: 10.1093/treephys/tpab175
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between species change the uptake of ammonium and nitrate inAbies faxonianaandPicea asperata

Abstract: Plant nitrogen (N) uptake is affected by plant–plant interactions, but the mechanisms remain unknown. 15N-labeled technique was used in a pot experiment to analyze the uptake rate of ammonium (NH4+) and nitrate (NO3−) by Abies faxoniana and Picea asperata in single-plant mode, intraspecific and interspecific interactions. The results indicated that the effects of plant–plant interactions on N uptake rate depended on plant species and N forms. P. asperata had a higher N uptake rate of both N forms than A. faxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Here, we found that both species preferred to absorb NO 3 À -N across the two seasons and that the contribution of NO 3 À -N in organs and the whole plant was higher than NH 4 + -N (Figures 3, 6), which supported that conifers prefer NO 3 À than NH 4 + (Zhu et al, 2021;Hu et al, 2021a). The reasons are linked to high soil NO 3 À -N availability, solubility, and mobility, as well as an efficient NO 3 À -N translocation and the use of plants (Zhou et al, 2017;Zhu et al, 2021;Hu et al, 2021a). The consistency of seasonal N-uptake preference may be mainly attributed to the mobility and high availability of NO 3 À -N (Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Here, we found that both species preferred to absorb NO 3 À -N across the two seasons and that the contribution of NO 3 À -N in organs and the whole plant was higher than NH 4 + -N (Figures 3, 6), which supported that conifers prefer NO 3 À than NH 4 + (Zhu et al, 2021;Hu et al, 2021a). The reasons are linked to high soil NO 3 À -N availability, solubility, and mobility, as well as an efficient NO 3 À -N translocation and the use of plants (Zhou et al, 2017;Zhu et al, 2021;Hu et al, 2021a). The consistency of seasonal N-uptake preference may be mainly attributed to the mobility and high availability of NO 3 À -N (Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…On July and September 20, 2020, three replicates per treatment were randomly selected for labelling 15 N isotope tracers ( 15 NH 4 + or 15 NO 3 − ) and control, respectively (Figure 1b). The 15 N labelling process and the details of this experiment have been described by Hu et al (2021a). A labelling solution with 19 μmol mL −1 N containing 15 NH 4 Cl or K 15 NO 3 (99 atom%) was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations